Library Professional Skills and Utilization of Information Resources in Federal University Libraries - Martina Ekpenyong Ekeng; Patience Owere Ekpang (PREDESTINASI, 2021)
This study investigated the relationship between Library variables and utilization of information resources in federal university libraries in South-South, Nigeria. To achieve the purpose of this study, two research questions were raised and two hypotheses were formulated to guide the study. Ex-post facto research design was adopted for the study. The population of the study was 16620 students and a sample of 800 respondents was selected for the study. Stratified and purposive random sampling technique was used for the study. The results of the analyses revealed a significant relationship between weeding and selections of information resources. Based on these findings, it was recommended, among others that: weeding should be a regular exercise in the libraries to rid the shelves of irrelevant, obsolete and damaged information resources.